Persistence of power: Repeated multilateral bargaining with endogenous agenda setting authority - Marina Agranov; Christopher Cotton; Chloe Tergiman (Queen's University, Department of Economics, 2019)
In models of dynamic multilateral bargaining, the literature tends to focus on stationary subgame perfect or stationary Markov perfect equilibria, which restrict attention to forward-looking, history-independent strategies. Evidence supporting such refinements come from environments in which proposal power is exogenous and the incentives for players to develop cooperative relationships are minimized. However, in many environments including legislative bargaining, agenda setting power is endogenous and it is common place for players to form coalitions and establish reputations. Through a series of lab experiments, we show that in repeated environments, standard equilibrium refinements may predict some aspects of the data when outcomes when proposal power is randomly assigned, but do not predict outcomes when proposal power is endogenous.
Keywords: C78; D02; C92; 330; stationary equilibrium; dynamic bargaining; repeated games; laboratory experiment